Suicidal Ideation Among Medical Students: Prevalence and Predictors - Torres, Albina R.; Campos, Luana M.; Lima, Maria Cristina P.; Ramos-Cerqueira, Ana Teresa A. (Lippincott Williams & Wilkins, 2018)
Suicide is one of the leading causes of death among medical students, second to car accidents. We investigated the prevalence and predictors of suicidal ideation (SI) among medical students in Brazil. This is a cross-sectional study with 475 medical students of a public university. The research protocol included data on sociodemographics and academic life, and structured instruments to assess social support and psychopathological symptoms, including the Beck Depression Inventory (BDI). The outcome was evaluated using the BDI suicide item. Bivariate analyses were followed by logistic regression. SI was present in 34 participants (7.2%). In the logistic regression, SI remained associated with living alone, thoughts of abandoning the course, moderate or severe depressive symptoms, and probable obsessive-compulsive disorder. SI is frequent among medical students and can be identified with a simple screening question. Special attention should be given to students living alone, with thoughts of abandoning the course, and relevant depressive or obsessive-compulsive symptoms.
Keywords: Suicidal ideation; suicidality; depressive symptoms; medical students; university students